REPLACEMENT OF FISH MEAL BY CANOLA MEAL IN DIETS FOR MAJOR CARPS IN FERTILIZED PONDS - S. ABBAS, I. AHMED, M. HAFEEZ-UR-REHMAN AND A. MATEEN (Pakistan Veterinary Journal, 2008)
This study was conducted in three earthen ponds to evaluate the replacement of fish meal by low cost plant protein (canola meal) for major carps in semi-intensive culture system. Each pond was fertilized with cattle manure at the rate of 0.16g N/100g wet fish body weight daily. A control diet (30% CP), formulated by using fish meal, cotton seed meal, maize gluten and rice polish, was designated as T1, while in T2 and T3, the fish meal was replaced with canola meal by 20 and 40%, respectively. Feeding was done at the rate of 4% of wet fish body weight daily for five months. The overall average weight gains in T1, T2 and T3 for three fish species i.e. Labeo rohita, Cirrhinus mrigala and Catla catla were 356.6 ± 15.12, 332.6 ± 14.32 and 362.4 ± 12.12; 320.4 ± 14.03, 305.6 ± 14.03 and 337.1 ± 16.02; and 284.6 ± 13.07, 282.2 ± 15.13 and 305.1 ± 17.43g, respectively. Net fish yields (all the species together) were 1529.5 ± 13.93, 1327.0 ± 12.19 and 1122.5 ± 10.28 Kg/ha/year under T1, T2 and T3, respectively. The gross fish production was calculated as 2338.5 ± 12.49, 2137.5 ± 11.65 and 1931.5 ± 13.01 Kg/ha/year in T1, T2 and T3 pond, respectively. In all the treatments, Catla catla showed better growth performance, followed by Labeo rohita and Cirrhinus mrigala. The treated ponds caused a decrease in fish production when replacement of fish meal was done with canola meal.